2014
DOI: 10.1111/inr.12097
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion strategies for families with adolescents orphaned by HIV and AIDS

Abstract: Purpose This paper aims to explore and describe health promotion strategies for adolescents orphaned by human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS), as well as the evaluation thereof. Introduction and Background Among the Sub‐Saharan countries, such as Swaziland, Botswana and Lesotho, South Africa is rated as fourth in the list of countries with the highest number of people living with HIV and AIDS. Method The study employed phenomenological qualitative design. The populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…During the participants' visits, they assisted families with patient care, while assessing the environment, educating the family and the clients on HIV and AIDS care and support, disease prevention and the treatment they were taking (Peu, 2014). The author further confirmed that health promoters assessed and assisted clients in establishing their own vegetable gardens.…”
Section: Conducting Health Promoting Home Visitsmentioning
confidence: 76%
See 4 more Smart Citations
“…During the participants' visits, they assisted families with patient care, while assessing the environment, educating the family and the clients on HIV and AIDS care and support, disease prevention and the treatment they were taking (Peu, 2014). The author further confirmed that health promoters assessed and assisted clients in establishing their own vegetable gardens.…”
Section: Conducting Health Promoting Home Visitsmentioning
confidence: 76%
“…During the discussions, the participants realised that their contributions were interlinked and overlapping with other nursing categories. They further emphasised that they worked with social workers during health promoting home visits and door to door campaigns (Peu, 2014). Similarly Kemppainen, Tossavainen and Turunen (2012) confirm that the role of nurses involves clinical nursing practice, follow up treatment, patient education and illness prevention.…”
Section: Conducting Health Promoting Home Visitsmentioning
confidence: 94%
See 3 more Smart Citations